The beneficial effects of stingless bee honey from heterotrigona itama against metabolic changes in rats fed with high-carbohydrate and high-fat diet - Nur Zuliani Ramli; Chin, Kok-Yong; Khairul Anwar Zarkasi; Fairus Ahmad (MDPI, 2019)
Metabolic syndrome (MetS) is a group of conditions including central obesity, hyperglycemia, dyslipidemia, and hypertension that increases the risk for cardiometabolic diseases. Kelulut honey (KH) produced by stingless honey bees has stronger antioxidant properties compared to other honey types and may be a functional food against MetS. This study aimed to determine the efficacy of KH in preventing metabolic changes in rats with MetS induced by high-carbohydrate and high-fat (HCHF) diet. Male Wistar rats were randomly assigned to the control (C), HCHF diet-induced MetS (S), and MetS supplemented with KH (K) groups. The K group was given KH (1 g/kg/day) for eight weeks. Compared to the control, the S group had significant higher omental fat mass, serum triglyceride, systolic blood pressure, diastolic blood pressures, adipocyte area, and adipocyte perimeter (p < 0.05). KH supplementation significantly prevented these MetS-induced changes at week 16 (p < 0.05). Several compounds, including 4-hydroxyphenyl acetic acid, coumaric and caffeic acids, had been detected via liquid chromatography-mass spectrometry analysis that might contribute to the reversal of these changes. The beneficial effects of KH against MetS-induced rats provide the basis for future KH research to investigate its potential use in humans and its molecular mechanisms in alleviating the disease.